A Review of Rat Models of Avascular Necrosis of the Femoral Head Treated with Natural Extracts - Go-Woon Kim; Hyoung-Yong Park; Yeon-Cheol Park (MEDrang Inc., 2022)
To determine the effect of Korean medicine treatment of avascular necrosis of the femoral head (ANFH) this study reviewed both single ingredients and bioactive compounds in the treatment of ANFH in a rat model. Literature was retrieved from PubMed and Google Scholar using the keywords "femur head necrosis," "natural extract," and "rat." The data from studies analyzed included: rats' characteristics, development methods of ANFH, natural extracts administration, observation methods, and outcome indicators. Two independent researchers screened all articles retrieved and 26 studies were chosen. The most used rat species was the Sprague Dawley rat (76.9%). To induce ANFH, steroid injections (46.2%), and oral gavage (53.8%) were typically used. Studies focused mainly on factors affecting bone formation (65.3%), and apoptosis (53.8%). Research on ANFH focused on using traditional natural substances mentioned in classical literature to confirm its effectiveness against anti-inflammation, osteogenesis, and cell death. ANFH has a diverse etiology, therefore research models such as genetic analysis of human-derived samples from ANFH patients may shed more light on the condition. Moreover, research into herbal medicines and pharmacoacupuncture treatment of ANFH should precede.